Primary, cardiac, fibroblastic osteosarcoma: A case report. Issue 1 (January 2018) - Li, Yangyang; Ye, Teng; Gu, Qianru; Dong, Lei; Chen, Guorong; Lu, Shanshan
Abstract: Rationale: Primary cardiac osteosarcoma is a rare tumor. To our knowledge, only 15 cases have been reported in the literature in the past 10 years. We describe a case of primary, cardiac, fibroblastic osteosarcoma in a 42-year-old woman. Patient concerns: A 42-year-old woman with a 10-day history of chest pain. Intraoperatively, a mass was found originating from the ostium of the left inferior pulmonary vein in the left atrium, extending to the mitral orifice. Histologically, the tumor contained variable amounts of spindle cells and osseous differentiation in different areas. Primary, cardiac fibroblastic osteosarcoma had the typical appearance of interlacing hyperchromatic spindle-shaped stromal cells associated with osseous matrix. Diagnoses: According to the clinicopathological features, diagnosis of primary, cardiac fibroblastic osteosarcoma was made. Interventions: Wide surgical excision of the mass was performed. Outcomes: Three months after the operation, transthoracic echocardiography demonstrated a 3.2 cm × 2 cm recurrent mass in the wall of the left atrium (LA). She died shortly afterwards as a result of the local disease recurrence. Lessons: In this report, we describe a rare case of primary, cardiac fibroblastic osteosarcoma, and findings are helpful for the pathologists would like to further identify the clinicopathological features of this rare tumor.